Justifying surgery's last taboo: the ethics of face transplants. Issue 2 (30th January 2007) - Freeman, Michael; Abou Jaoudé, Pauline
Abstract : Should face transplants be undertaken? This article examines the ethical problems involved from the perspective of the recipient, looking particularly at the question of identity, the donor and the donor's family, and the disfigured community and society more generally. Concern is expressed that full face transplants are going ahead.